Thomas Corwin correspondence - Corwin, Thomas, 1794-1865.
Correspondence received during Corwin's tenure as U.S. secretary of the treasury in Millard Fillmore's administration. Subjects include appointments to and removals from office, Whig politics, and financial and commercial policies of the Fillmore administration. Correspondents include George C. Bates, Leslie Combs, Moses B. Corwin, Simeon Draper, Thomas Ewing, William D. Gallagher, William Grandin, William J. Grayson, Moses Hicks Grinnell, Washington Hunt, Reverdy Johnson, George P. Kane, William David Lewis, John McLean, Francis Mallory, Willie Person Mangum, Edward Deering Mansfield, Hugh Maxwell, Henry Dunning Moore, John Henry Clay Mudd, James Alfred Pearce, Aaron F. Perry, George D. Prentice, William J. Reese, William Henry Seward, Truman Smith, Daniel Webster, Thurlow Weed, Hugh White, John J. Williams, William Henry Winder, and John C. Wright.
Lawyer, Ohio governor, U.S. representative and senator from Ohio, and U.S. secretary of the treasury.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bates, George C. -- Correspondence; Combs, Leslie, -- 1793-1881 -- Correspondence; Corwin, Moses B. -- 1790-1872 -- Correspondence; Draper, Simeon, -- 1804-1866 -- Correspondence; Ewing, Thomas, -- 1789-1871 -- Correspondence; Fillmore, Millard, -- 1800-1874.; Gallagher, William D. -- 1808-1894 -- Correspondence; Grandin, William -- Correspondence; Grayson, William J. -- 1788-1863 -- Correspondence; Grinnell, Moses Hicks, -- 1803-1877 -- Correspondence; Hunt, Washington, -- 1811-1867 -- Correspondence; Johnson, Reverdy, -- 1796-1876 -- Correspondence; Kane, George P. -- Correspondence; Lewis, William David, -- 1792-1881 -- Correspondence; McLean, John, -- 1785-1861 -- Correspondence; Mallory, Francis, -- 1807-1860 -- Correspondence; Mangum, Willie Person, -- 1792-1861 -- Correspondence; Mansfield, Edward Deering, -- 1801-1880 -- Correspondence; Maxwell, Hugh, -- 1787-1873 -- Correspondence; Moore, Henry Dunning, -- 1817-1887 -- Correspondence; Mudd, John Henry Clay, -- 1821-1866 -- Correspondence; Pearce, James Alfred, -- 1805-1862 -- Correspondence; Perry, Aaron F. -- 1815-1893 -- Correspondence; Prentice, George D. -- 1802-1870 -- Correspondence; Reese, William J. -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Smith, Truman, -- 1791-1884 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Weed, Thurlow, -- 1797-1882 -- Correspondence; White, Hugh, -- 1798-1870 -- Correspondence; Williams, John J. -- Correspondence; Winder, William Henry, -- 1775-1824 -- Correspondence; Wright, John C. -- 1783-1861 -- Correspondence; United States. -- Department of the Treasury; Whig Party (U.S.); United States -- Economic policy; United States -- Politics and government -- 1849-1853.; Cabinet officers; Governors -- Ohio; Lawyers; Representatives, U.S. Congress -- Ohio; Senators, U.S. Congress -- Ohio